Maximization of fructooligosaccharides and β-fructofuranosidase production by Aspergillus japonicus under solid-state fermentation conditions - Mussatto, Solange I. (2013)
The conditions of temperature, moisture content, and inoculum rate able to maximize the production of fructooligosaccharides (FOS) and β-fructofuranosidase (FFase) enzyme by solid-state fermentation were established. Fermentation assays were performed using the support material (coffee silverskin) moistened to 60, 70, or 80 % with a 240-g/l sucrose solution and inoculated with a spore suspension of Aspergillus japonicus to obtain 2 × 10 5, 2 × 10 6, or 2 × 10 7 spores/gram dry material. The fermentation runs were maintained under static conditions at 26, 30, or 34 °C during 20 h. The moisture content did not influence the FOS and FFase production; however, temperature between 26 and 30 °C and inoculum rate of approximately 2 × 10 7 spores/gram dry material maximized the results (FOS = 208.8 g/l with productivity of 10.44 g/l h; FFase = 64.12 units U/ml with productivity of 4.0 U/ml h). These results are considerably higher than those obtained under no optimized fermentation conditions and represent an important contribution for the establishment of a new industrial process for FOS and FFase production.